Synthesis and characterization of Co-Fe nanocrystalline magnetic films electrodeposited from electrolyte solution containing sodium saccharin - Teh, Seoh Hian; Yaacob, Iskandar Idris (Institute of Electrical and Electronics Engineers ( IEEE ), 2011)
Cobalt-iron (Co-Fe) alloy thin films (Co100-x-Fex with x=0 , 6, 11, 14 and 18) were electrodeposited on brass substrates from sulfate plating baths containing saccharin salt. The electrolyte in the synthesis process consists of mixtures of FeSO4.7H2O , CoSO4.6H2O, NaCl and H3BO3. Various concentrations of FeSO4 were added to the plating solution to deposit films with different alloy compositions. Saccharin (C6H 4CONHSO2) was also added as a grain refining agent to improve the quality of deposits. Energy dispersive X-ray spectroscopy (EDS) analyses showed that the compositions of the electrodeposits corresponded to the concentration of FeSO4 in the electrolytic bath. X-ray diffraction (XRD) results showed that the crystallographic structure of the films was dependent on the composition of the alloy. Calculation of crystallite size from X-ray peak broadening showed that the crystallite sizes were within the range of 10-99 nm. Scanning electron microscopy (SEM) results showed that films with higher Fe content exhibited irregular granule shapes. The thicknesses of the thin films were about 50 μm as determined by SEM measurements of the films' cross section. Atomic force microscopy (AFM) results showed rougher granular surfaces for Co-Fe films with higher Fe content. A similar behavior was observed by SEM. Magnetic force microscopy (MFM) showed that the domain pattern was stripe structure for Co and Co94-Fe6 films. The structure changed to granular domain structures with increasing iron content. The best soft magnetic properties with high saturation magnetizations and low coercivities were obtained when BCC and FCC phases of Co-Fe system coexisted.